The new solar system : ice worlds, moons, and planets redefined - Daniels, Patricia, 1955-; Schneider, Howard (Washington, D.C. : National Geographic Society, 2010)
Aimed at the popular audience by experienced astronomy author Patricia and highlighted by 160 photographs, diagrams and maps, this guide explores every corner of Earth's planetary neighborhood, from the fiery sun at its center to the dark, icy realm where interstellar space begins. It's a state-of-the-art observation of the solar system as we know it today and a knowledgeable forecast of what to expect in the future, from Pluto's demotion to plutoid to the upcoming Moon mission, the likelihood of a manned expedition to Mars, and much more. From breathtaking photographs to detailed explanatory diagrams to expert essays, fascinating sidebars, and informative fact boxes, this is not just an easy-to-use reference, but also a visually stunning volume to fire the imagination of even the most casual reader.--From publisher description.
Explores the new technologies and discoveries that are showing us an ever more detailed vision of the solar system, in a resource that also includes diagrams, maps, essays, sidebars, and fact boxes.
Wandering stars -- The sun -- The inner planets -- Rocky dwarf planets -- The ringed planets -- Icy dwarf planets -- Are we alone? -- Exploring our home and beyond : a special supplement to The new solar system.
Expanded ed. includes (p. [225]-272): Exploring our home and beyond : a special supplement to The new solar system / Howard Schneider.
Includes bibliographical references (p. 214) and index.
Keywords: Solar system; Solar system -- Pictorial works